Ausgezeichnete Übersetzungen aus dem Deutschen im Übersetzungswettbewerb zu Ehren von Prof. Boris Paraschkewow - Kileva-Stamenova, Reneta (Zeitschrift „Germanistik und Skandinavistik“ / Journal for German and Scandinavian Studies, 2025)
In March 2025, the German Philology program at Sofia University St. Kliment Ohridski announced its fourth Student Translation Competition from German into Bulgarian. The competition is dedicated to the memory of Prof. Boris Parashkevov (1938–2021), a long-time professor in German Philology, a prominent Germanist of international renown, a specialist in diachronic linguistics, etymology, history, and historical grammar of the German language, who left behind a valuable body of translations from German and Finnish that will remain an example of a professional approach to translation and a mastery of the translator’s craft.